POLA KEPEMIMPINAN YANG EFEKTIF DAN IMPLIKASINYA TERHADAP MULTIPLIKASI KETUA FAMILY CARE MASA KINI - Suhendra suhendra; Yohanes Aloysius Da (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
This writing aims to examine Effective Leadership Patterns, which aims to find out the direct implications for the leadership of today's Family Care Chairs in the process of development and multiplication of both groups and also the leaders who will become the new Family Care Chairs. Becoming an effective leader in the Family Care group is very important so that each congregation can be shepherded well, at the same time the existing congregation is directed and prepared to become an effective leader in this current era. In writing this scientific work, appropriate research methods are needed, so the author uses qualitative research methods. By using basic theory from various book sources. The author also collected data in the field using interview methods with participants who were in direct contact with the current head of Family Care.